OCA optical adhesive and preparation method thereof
By using a specific combination of raw materials and light -induced agents to cause a co -concentration reaction to form multiple interoperability network structures, the existing OCA optical adhesives are insufficient weather resistance and poor environmental performance. And oil resistance.
Patent Information
- Application Number
- CN202411377173.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-21
AI Technical Summary
The existing OCA optical adhesives have insufficient weather resistance, easy yellowing, limited adhesive performance and performance stability, and poor environmental protection performance, resulting in the swelling of the glue layer, mechanical properties and light transmittance during long-term use, affecting the reliability of the equipment. and durability.
Uses include acrylate-terminated hyperbranched silicone-modified polyurethane, allyl succinimidyl carbonate, hexafluorobisphenol A diacrylate, 1,3-bis(oxyethylmethyl)-5 -(2-propenyl)-1,3,5-triazine-2,4 , a combination of raw materials such as 6(1H,3H,5H)-trione, 2,2'-bis(trifluoromethyl)diaminobiphenyl, etc., uses a photoinitiator to initiate a copolymerization and curing reaction to form a multiple interpenetrating network structure. Improve the weather resistance, oil resistance and mechanical properties of adhesives.
OCA optical adhesives with good adhesion performance have good weather resistance, environmental protection performance and oil resistance, extending the service life of the product and improving the reliability and durability of the equipment.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adhesives, and in particular to an OCA optical adhesive and a preparation method thereof. Background Art
[0002] With the increasing popularity of touch screen electronic products, the touch screen industry has become the hottest industry today and is developing rapidly, so the demand for OCA optical adhesives used in touch screens has also increased dramatically. OCA optical adhesives are widely used in the assembly of optical devices such as touch screens, navigation systems, and mobile phones due to their advantages such as high clarity, high optical transparency, and high adhesion. They are one of the key materials for connecting display modules, glass substrates, touch screens, and other display units.
[0003] Existing OCA optical adhesives have more or less problems such as insufficient weather resistance, easy yellowing, limited bonding performance and performance stability, and poor environmental performance. During long-term use, the adhesive layer is prone to swelling, mechanical properties and light transmittance decline, which in turn leads to defects such as reduced reliability and durability of the corresponding equipment.
[0004] In order to solve the above problems, the Chinese invention patent with the authorization announcement number CN116239992B discloses a bending-resistant organic silicon OCA optical adhesive and its preparation method, which includes the following components by weight percentage: 10-20% methyl vinyl polysiloxane; 25-35% VMQ resin; 2-3% tackifying resin; 1-2.5% silane coupling agent; 1.5-2.5% hydrogenated silicone oil; 1-2.5% crosslinking agent; 3-5% catalyst; 0.05-0.25% inhibitor; 35-45% toluene. The application uses methyl vinyl polysiloxane, VMQ resin and silane coupling agent to mix and prepare the organic silicon main body, and obtains the organic silicon OCA optical adhesive with excellent bending resistance, high peel strength and good light transmittance by adding and curing hydrogenated silicone oil, and the preparation method is simple to operate and has good industrial promotion prospects. However, the use of organic solvent toluene makes the product have poor environmental performance, and the manufactured OCA optical adhesive also has defects in durability and oil resistance that need to be further improved.
[0005] It can be seen that the development of an OCA optical adhesive with good bonding performance, sufficient weather resistance and environmental protection performance, and good oil resistance and its preparation method meets market demand, has broad market value and application prospects, and is of great significance to promoting the development of the optical adhesive field. Summary of the invention
[0006] In view of this, the technical problem to be solved by the present invention is to provide an OCA optical adhesive with good bonding performance, sufficient weather resistance and environmental protection performance, and good oil resistance, and a preparation method thereof.
[0007] The invention provides an OCA optical adhesive, which is prepared from the following raw materials in parts by weight: 35-45 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 2-4 parts of allyl succinimidyl carbonate, 1-3 parts of hexafluorobisphenol A diacrylate, 3-5 parts of 1,3-bis(oxiranylmethyl)-5-(2-propylene)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 3-5 parts of 2,2'-bis(trifluoromethyl)diaminobiphenyl, 6-8 parts of other polymerizable monomers, 20-30 parts of a diluent, 0.6-1.2 parts of a photoinitiator, 0.5-1 parts of an antioxidant, and 0.5-1 parts of a defoaming agent.
[0008] Preferably, the defoaming agent is one or more of tributyl phosphate, defoaming agent Deqian 3100, and defoaming agent BYK088.
[0009] Preferably, the antioxidant is any one or more of IRGANOX 1726, IRGANOX 1010, and IRGANOX 1076 produced by BASF of Germany.
[0010] Preferably, the photoinitiator is any one or more of IRGACURE 184, LUCIRIN TPO, and IRGACURE 819 from BASF, Germany.
[0011] Preferably, the diluent is a mixture of methyl methacrylate, butyl methacrylate and hydroxypropyl methacrylate in a mass ratio of 1:(0.8-1.2):(1-2).
[0012] Preferably, the other polymerizable monomer is at least one of N-vinyloxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, tetrahydrofurfuryl acrylate, 4-methyl-5-vinylthiazole, and acrylonitrile.
[0013] Preferably, there is no special requirement for the source of the acrylate-terminated hyperbranched silicone-modified polyurethane. In one embodiment of the present invention, the acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 of Chinese invention patent with authorization announcement number CN111393608B.
[0014] Another object of the present invention is to provide a method for preparing the OCA optical adhesive, comprising the following steps: mixing the raw materials uniformly by weight, vacuuming and degassing for 1-2 hours, and finally standing and degassing before storing to obtain the OCA optical adhesive.
[0015] Due to the application of the above technical solution, the present invention has the following beneficial effects: (1) The preparation method of the OCA optical adhesive disclosed in the present invention only requires mixing the raw materials evenly and then degassing and defoaming. No special equipment is required, the capital investment is small, the energy consumption is low, the process is simple and easy to operate, the preparation efficiency and the qualified rate of finished products are high, and it is suitable for continuous large-scale production and has a high value for promotion and application.
[0016] (2) The OCA optical adhesive disclosed in the present invention is made of the following raw materials in parts by weight: 35-45 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 2-4 parts of allyl succinimidyl carbonate, 1-3 parts of hexafluorobisphenol A diacrylate, 3-5 parts of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 3-5 parts of 2,2'-bis(trifluoromethyl)diaminobiphenyl, 6-8 parts of other polymerizable monomers, 20-30 parts of diluent, 0.6-1.2 parts of photoinitiator, 0.5-1 parts of antioxidant, and 0.5-1 parts of defoaming agent. Through the mutual coordination and joint action of various raw materials, the prepared OCA optical adhesive has good bonding performance, sufficient weather resistance and environmental protection performance, and good oil resistance; the selected raw materials do not contain volatile organic harmful solvents, so that the product is safe and environmentally friendly to use; through the reasonable selection of raw material types and dosage ratios, hyperbranched silicone modified polyurethane, succinimidyl carbonate, hexafluorobisphenol A, ester group, triazone, fluorinated biphenyl, oxazolidinone, amphoteric organic ion salt, tetrahydrofurfuryl ester, thiazole and nitrile structure are introduced into the film at the same time, and these structures, under the multiple effects of electronic effect, steric effect and conjugation effect, make the prepared product have better bonding performance, better weather resistance and oil resistance.
[0017] (3) In the OCA optical adhesive disclosed in the present invention, the raw materials containing unsaturated olefinic bonds can undergo copolymerization and curing reaction under the action of a photoinitiator. At the same time, the 1,3-bis(oxiranylmethyl)-5-(2-propylene)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione containing an epoxy group can undergo an epoxy ring-opening reaction with the 2,2'-bis(trifluoromethyl)diaminobiphenyl containing an amino group, so that the adhesive film formed after the adhesive is cured contains multiple interpenetrating network structures, which effectively improves its weather resistance, oil resistance and mechanical properties.
[0018] (4) The OCA optical adhesive disclosed in the present invention, wherein the diluent is a mixture of methyl methacrylate, butyl methacrylate and hydroxypropyl methacrylate in a mass ratio of 1:(0.8-1.2):(1-2); the other polymerizable monomers are at least one of N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, tetrahydrofurfuryl acrylate, 4-methyl-5-vinylthiazole and acrylonitrile; through the reasonable selection of these raw material compositions, they can have good compatibility with other raw materials, ensure the transparency of the obtained product, and enable them to better interact with each other, thereby further improving the weather resistance, oil resistance and bonding performance of the adhesive product. DETAILED DESCRIPTION
[0019] The following description is used to disclose the present invention so that those skilled in the art can implement the present invention. The preferred embodiments described below are only examples, and those skilled in the art may think of other obvious variations. Example 1
[0020] An OCA optical adhesive comprises the following raw materials in parts by weight: 35 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 2 parts of allyl succinimidyl carbonate, 1 part of hexafluorobisphenol A diacrylate, 3 parts of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 3 parts of 2,2'-bis(trifluoromethyl)diaminobiphenyl, 6 parts of other polymerizable monomers, 20 parts of diluent, 0.6 parts of photoinitiator, 0.5 parts of antioxidant and 0.5 parts of defoamer.
[0021] The defoaming agent is tributyl phosphate; the antioxidant is IRGANOX 1726 from BASF of Germany; the photoinitiator is IRGACURE 184 from BASF of Germany; and the diluent is a mixture of methyl methacrylate, butyl methacrylate and hydroxypropyl methacrylate in a mass ratio of 1:0.8:1.
[0022] The other polymerizable monomers are N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, tetrahydrofurfuryl acrylate, 4-methyl-5-vinylthiazole, and acrylonitrile mixed in a mass ratio of 1:2:1:3:2; the acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN111393608B.
[0023] A preparation method of the OCA optical adhesive comprises the following steps: mixing the raw materials uniformly according to weight, vacuuming and degassing for 1 hour, and finally standing and degassing before storing to obtain the OCA optical adhesive. Example 2
[0024] An OCA optical adhesive comprises the following raw materials in parts by weight: 37 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 2.5 parts of allyl succinimidyl carbonate, 1.5 parts of hexafluorobisphenol A diacrylate, 3.5 parts of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 3.5 parts of 2,2'-bis(trifluoromethyl)diaminobiphenyl, 6.5 parts of other polymerizable monomers, 23 parts of diluent, 0.8 parts of photoinitiator, 0.6 parts of antioxidant and 0.7 parts of defoaming agent.
[0025] The defoamer is Deqian 3100; the antioxidant is IRGANOX 1010 produced by BASF of Germany; the photoinitiator is LUCIRIN TPO produced by BASF of Germany; the diluent is a mixture of methyl methacrylate, butyl methacrylate and hydroxypropyl methacrylate in a mass ratio of 1:0.9:1.2.
[0026] The other polymerizable monomers are N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, tetrahydrofurfuryl acrylate, 4-methyl-5-vinylthiazole, and acrylonitrile, which are mixed in a mass ratio of 1:1:1:3:5; the acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN111393608B.
[0027] A preparation method of the OCA optical adhesive comprises the following steps: mixing the raw materials uniformly according to weight, vacuuming and degassing for 1.2 hours, and finally standing and degassing before storing to obtain the OCA optical adhesive. Example 3
[0028] An OCA optical adhesive comprises the following raw materials in parts by weight: 40 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 3 parts of allyl succinimidyl carbonate, 2 parts of hexafluorobisphenol A diacrylate, 4 parts of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 4 parts of 2,2'-bis(trifluoromethyl)diaminobiphenyl, 7 parts of other polymerizable monomers, 25 parts of diluent, 0.9 parts of photoinitiator, 0.8 parts of antioxidant and 0.8 parts of defoaming agent.
[0029] The defoamer is defoamer BYK088; the antioxidant is IRGANOX 1076 from BASF of Germany; the photoinitiator is IRGACURE 819 from BASF of Germany; the diluent is a mixture of methyl methacrylate, butyl methacrylate and hydroxypropyl methacrylate in a mass ratio of 1:1:1.5.
[0030] The other polymerizable monomers are N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, tetrahydrofurfuryl acrylate, 4-methyl-5-vinylthiazole, and acrylonitrile mixed in a mass ratio of 1:3:5:2:2; the acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN111393608B.
[0031] A preparation method of the OCA optical adhesive comprises the following steps: mixing the raw materials uniformly according to weight, vacuuming and degassing for 1.5 hours, and finally standing and degassing before storing to obtain the OCA optical adhesive. Example 4
[0032] An OCA optical adhesive comprises the following raw materials in parts by weight: 43 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 3.5 parts of allyl succinimidyl carbonate, 2.5 parts of hexafluorobisphenol A diacrylate, 4.5 parts of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 4.5 parts of 2,2'-bis(trifluoromethyl)diaminobiphenyl, 7.5 parts of other polymerizable monomers, 28 parts of diluent, 1 part of photoinitiator, 0.9 part of antioxidant and 0.9 part of defoaming agent.
[0033] The defoamer is a mixture of tributyl phosphate, defoamer Deqian 3100 and defoamer BYK088 in a mass ratio of 1:2:3; the antioxidant is a mixture of IRGANOX 1726, IRGANOX 1010 and IRGANOX 1076 of BASF of Germany in a mass ratio of 1:3:5; the photoinitiator is a mixture of IRGACURE 184, LUCIRIN TPO and IRGACURE 819 of BASF of Germany in a mass ratio of 2:1:3; the diluent is a mixture of methyl methacrylate, butyl methacrylate and hydroxypropyl methacrylate in a mass ratio of 1:1.1:1.8.
[0034] The other polymerizable monomers are N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, tetrahydrofurfuryl acrylate, 4-methyl-5-vinylthiazole, and acrylonitrile, which are mixed in a mass ratio of 1:3:2:5:1; the acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN111393608B.
[0035] A preparation method of the OCA optical adhesive comprises the following steps: mixing the raw materials uniformly according to weight, vacuuming and degassing for 1.9 hours, and finally standing and degassing before storing to obtain the OCA optical adhesive. Example 5
[0036] An OCA optical adhesive comprises the following raw materials in parts by weight: 45 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 4 parts of allyl succinimidyl carbonate, 3 parts of hexafluorobisphenol A diacrylate, 5 parts of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 5 parts of 2,2'-bis(trifluoromethyl)diaminobiphenyl, 8 parts of other polymerizable monomers, 30 parts of diluent, 1.2 parts of photoinitiator, 1 part of antioxidant and 1 part of defoaming agent.
[0037] The defoaming agent is tributyl phosphate; the antioxidant is IRGANOX 1726 from BASF of Germany; the photoinitiator is IRGACURE 184 from BASF of Germany; and the diluent is a mixture of methyl methacrylate, butyl methacrylate and hydroxypropyl methacrylate in a mass ratio of 1:1.2:2.
[0038] The other polymerizable monomers are N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, tetrahydrofurfuryl acrylate, 4-methyl-5-vinylthiazole, and acrylonitrile mixed in a mass ratio of 3:1:2:2:2; the acrylate-terminated hyperbranched silicone-modified polyurethane is prepared according to the method of Example 1 of the Chinese invention patent with authorization announcement number CN111393608B.
[0039] A preparation method of the OCA optical adhesive comprises the following steps: mixing the raw materials uniformly according to weight, vacuuming and degassing for 2 hours, and finally standing and degassing before storing to obtain the OCA optical adhesive.
[0040] Comparative Example 1 An OCA optical adhesive and a preparation method thereof, which are substantially the same as those in Example 1, except that no other polymerizable monomers are added.
[0041] Comparative Example 2 An OCA optical adhesive and a preparation method thereof, which are substantially the same as those in Example 1, except that allyl succinimidyl carbonate and hexafluorobisphenol A diacrylate are not added.
[0042] In order to further illustrate the beneficial technical effects of the OCA optical adhesive involved in each embodiment of the present invention, relevant performance tests are performed on the OCA optical adhesive involved in Examples 1-5 and Comparative Examples 1-2. The test results are shown in Table 1. The test method is as follows: (1) Two pieces of optical glass with a length of 115 mm, a width of 60 mm, and a thickness of 1 mm were filled with 100 μm thick OCA optical adhesive at 3000 mJ / cm 2 The sample was cured under ultraviolet light conditions and placed in a UV aging box at 60°C and 0.86w / cm 2 , place it for 500 hours, and test the yellowness index of the sample after aging.
[0043] (2) Each product was coated on a 25 μm PET film with a dry coating thickness of 25 μm; then dried at 80°C for 2 min, cured under ultraviolet light with a wavelength of 250 nm for 30 min, and then aged at 40°C for 3 days; the adhesion, retention and initial adhesion were tested in accordance with the current national standards of my country, wherein the adhesion test conditions were as follows: for SUS, 180° peeling, 300 mm / min, 23°C, 50% RH; the retention test conditions were as follows: for SUS, area 25 mm×25 mm, 40°C, load 1 kg, 1 hour; the initial adhesion test conditions were as follows: J.Dow method, 23°C, 50% RH.
[0044] (3) Oil resistance: Place the cured sample (curing conditions: drying at 80°C for 2 min, curing under ultraviolet light with a wavelength of 250 nm for 30 min, and then aging at 40°C for 3 days) in No. 75 aviation gasoline at room temperature for 10 days and observe the sample status. If no swelling or discoloration occurs, the oil resistance is passed. If swelling, discoloration or bubbles are observed on the sample, the oil resistance is failed.
[0045] Table 1
[0046] It can be seen from Table 1 that the OCA optical adhesives disclosed in the embodiments of the present invention have better bonding performance, yellowing resistance and oil resistance than the comparative products; the combined use of other polymerizable monomers, allyl succinimidyl carbonate and hexafluorobisphenol A diacrylate is beneficial to improving the above properties.
[0047] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions only describe the principles of the present invention. The present invention may be subject to various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements fall within the scope of the present invention. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.
Claims
1. An OCA optical adhesive, characterized in that: The invention comprises the following raw materials in parts by weight: 35-45 parts of acrylate-terminated hyperbranched silicone-modified polyurethane, 2-4 parts of allyl succinimidyl carbonate, 1-3 parts of hexafluorobisphenol A diacrylate, 3-5 parts of 1,3-bis(oxiranylmethyl)-5-(2-propenyl)-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, 3-5 parts of 2,2'-bis(trifluoromethyl)diaminobiphenyl, 6-8 parts of other polymerizable monomers, 20-30 parts of diluent, 0.6-1.2 parts of photoinitiator, 0.5-1 parts of antioxidant and 0.5-1 parts of defoaming agent.
2. The OCA optical adhesive according to claim 1, characterized in that: The defoaming agent is one or more of tributyl phosphate, defoaming agent Deqian 3100, and defoaming agent BYK088.
3. The OCA optical adhesive according to claim 1, characterized in that: The antioxidant is any one or more of IRGANOX 1726, IRGANOX 1010 and IRGANOX 1076 produced by BASF of Germany.
4. The OCA optical adhesive according to claim 1, characterized in that: The photoinitiator is any one or more of IRGACURE 184, LUCIRIN TPO, and IRGACURE 819 from BASF of Germany.
5. The OCA optical adhesive according to claim 1, characterized in that: The diluent is a mixture of methyl methacrylate, butyl methacrylate and hydroxypropyl methacrylate in a mass ratio of 1:(0.8-1.2):(1-2).
6. The OCA optical adhesive according to claim 1, characterized in that: The other polymerizable monomer is at least one of N-vinyl oxazolidinone, 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, tetrahydrofurfuryl acrylate, 4-methyl-5-vinylthiazole, and acrylonitrile.
7. A method for preparing the OCA optical adhesive according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: uniformly mixing the raw materials according to weight, vacuuming and degassing for 1-2 hours, and finally standing and degassing before storing to obtain the OCA optical adhesive.
Citation Information
Patent Citations
A method for preparing UV-curable silicone-modified hyperbranched polyurethane material
CN111393608B
A flexurally resistant silicone OCA optical adhesive and its preparation method
CN116239992B
Green and environment-friendly building mortar and preparation method thereof
CN117534385A
UV photocuring adhesive and preparation method thereof
CN118064086A
Anti-adhesion gauze and manufacturing method thereof
CN118087264A
Cited By
Green and environment-friendly building mortar and preparation method thereof
CN117534385A
UV photocuring adhesive and preparation method thereof
CN118064086A
UV photocuring OCA optical adhesive film and preparation method thereof
CN120098566A
Anti-aging antibacterial film and preparation method thereof
CN120192610A
Aging-resistant antibacterial film and preparation method thereof
CN120192610B